PENUMPUKAN PENYERAPAN ANGGARAN DI AKHIR TAHUN: FAKTOR PENYEBAB DAN DAMPAKNYA TERHADAP OPERASIONAL SKPD ( Kasus SKPD Se-Jawa Tengah ) - Dien Pamelasih, 11 4202 0109; Basukianto, Basukianto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the factors that cause stacking of utilization and impact caused by the stacking of budget utilization as well as to find a solution that must be done so that budget utilization in Central Java province SKPDs (local government working units) more effectively. Research technique used is quantitative descriptive method. The sample was 50 SKPDs in the Regional Government of Central Java Province. The data was collected using a Likert scale questionnaire 1-5. The data testing method used is validity testing by factor analysis, reliability test with Cronbach Alpha, and statistical description of the variables. The Results of the analysis and discussion showed that the most important factors causing the low budget utilization in SKPDs in Central Java province is the procurement of goods and services, including: 1) officials of procurement of goods and services that was too cautious in taking action led to extending the processing time; 2) the reluctance to become officials of the procurement of goods and services that is considered high risk concerning legal proceedings. Suggestions can be submitted to the Government of Central Java Province are: to distribute employees who have a certificate of the procurement of goods and services evenly to all departments; speed up the procurement process, and conduct procurement certification training in the earlier of year. Keywords: Causes, Impacts, and Budget utilization in SKPDs